1995
DOI: 10.1183/09031936.95.08020298
|View full text |Cite
|
Sign up to set email alerts
|

Delivering optimal care to the person with asthma: what are the key components and what do we mean by patient education?

Abstract: D De el li iv ve er ri in ng g o op pt ti im ma al l c ca ar re e t to o t th he e p pe er rs so on n w wi it th h a as st th hm ma a: : w wh ha at t a ar re e t th he e k ke ey y c co om mp po on ne en nt ts s a an nd d w wh ha at t d do o w we e m me ea an n b by y p pa at ti ie en nt t e ed du uc ca at ti io on n? ? ABSTRACT: The new understanding of the pathogenesis of asthma has led to an increasing perception of the disease as a chronic condition, rather than one consisting of acute exacerbations. Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Health promotion, disease prevention and community-based care are receiving more attention from Canadian of®cials looking to deliver more longterm health for less money (Makrides et al, 1997). Evidence that good communication and structured patient education can be cost-effective for conditions like asthma (Partridge, 1995) and arthritis (Lorig et al, 1993) will likely encourage the expansion of similar programs. Recognition of Precede ± Proceed model interactions has shaped the pattern of recently described patient care redesign at a large integrated teaching health care system located in the southeast, for example (Yingling & Trocino, 1997).…”
Section: Complications and Barriersmentioning
confidence: 99%
“…Health promotion, disease prevention and community-based care are receiving more attention from Canadian of®cials looking to deliver more longterm health for less money (Makrides et al, 1997). Evidence that good communication and structured patient education can be cost-effective for conditions like asthma (Partridge, 1995) and arthritis (Lorig et al, 1993) will likely encourage the expansion of similar programs. Recognition of Precede ± Proceed model interactions has shaped the pattern of recently described patient care redesign at a large integrated teaching health care system located in the southeast, for example (Yingling & Trocino, 1997).…”
Section: Complications and Barriersmentioning
confidence: 99%
“…Asthma and COPD still remain underdiagnosed and under-or badly treated worldwide, [9][10][11][12][13][14] and there remains a substantial discrepancy between the actual care provided and guideline-defined best treatment in patients with mild to moderate asthma or COPD in primary care. 15,16 There have been few studies investigating the quality of asthma and COPD care in Italian general practice. One study showed that a high number of patients with asthma and COPD have poor control of their disease, and suggested that Italian general practitioners (GPs) may misunderstand and misclassify the real level of disease severity and were therefore not modifying pharmacological treatment accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…2011;37(1): [19][20][21][22][23][24][25][26][27] or less), and had a low family income (70% of the families received less than 3 times the national minimum wage). Regarding smoking status, 62.6% had never smoked, 35.7% were former smokers, and only 1.7% currently smoked.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that a certain percentage of patients do not return to the hospital for this purpose, even after having expressed a desire to do so. (23,24) Inhaled corticosteroids are the most effective class of medications for the treatment of persistent asthma. (25) An important point in the present study was that the educational approach emphasized the need for long-term adherence to corticosteroid therapy, which resulted in an improvement in the use of these medications.…”
mentioning
confidence: 99%
See 1 more Smart Citation